(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. This study was conducted to evaluate the sensitivity and specificity of pyuria detection in centrifuged urine samples of patients on hemodialysis, and its relationship with urinary tract infection. Materials and Methods. Clean-catch midstream urine samples of 90 hemodialysis patients (34 women and 56 men) were obtained and divided into two parts for examination of urine sediment and urine culture. Pyuria was defined as the presence of more than 10 leukocytes per high-power field of microscope. Results. Ninety patients with a mean age of 52.8 ± 14.2 and a mean period of dialysis of 3.3 ± 2.3 years were studied. Forty-five participants had pyuria and only 16 (35.5%) of them had a positive urine culture for infection. Pyuria and urinary tract infection were present in 52.9% and 29.4% of the women and 48.2% and 10.7% of the men, respectively. The sensitivity and specificity of pyuria screening for urinary tract infection was 100% and 61.8%, respectively. The positive and negative predictive values were 35.5% and 100%, respectively. Conclusions. In patients on hemodialysis, because of the low specificity and positive predictive values, samples with positive pyuria should be cultured to confirm urinary tract infections.